RIMAPS Analysis of Filtered Images - Favret, Eduardo Alfredo (2012)
This research work analyzes how RIMAPS spectrum varies when a filter is applied on the image of a leaf surface. The stylize filter from the Adobe Photoshop software program is used. This filter identifies the areas of the image with significant transitions and emphasizes the edges with dark lines against a white background and is useful for highlighting the borders of cells and papillae.